2017
DOI: 10.1186/s12940-017-0266-9
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure in young adulthood and residential greenness in the early-life environment of twins

Abstract: BackgroundPrevious research shows that, besides risk factors in adult life, the early-life environment can influence blood pressure and hypertension in adults. However, the effects of residential traffic exposure and residential greenness in the early-life on blood pressure in young adulthood are currently unknown.MethodsAmbulatory (24-h) blood pressures of 278 twins (132 pairs) of the East Flanders Prospective Twins Study were obtained at the age of 18 to 25 years. Prenatal and adulthood residential addresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…A limited number of studies have quantified exposure to green spaces (e.g., parks) using land cover datasets to assess, for instance, the proportion of parks in a participant’s administrative boundary (e.g., Census tract) or within a given radius from the subject’s address [13,15,16,1824]. Other studies have assessed the road network distance between a participant’s home address and green spaces such as parks, forests, agricultural land, and others [10,14,16,2528].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies have quantified exposure to green spaces (e.g., parks) using land cover datasets to assess, for instance, the proportion of parks in a participant’s administrative boundary (e.g., Census tract) or within a given radius from the subject’s address [13,15,16,1824]. Other studies have assessed the road network distance between a participant’s home address and green spaces such as parks, forests, agricultural land, and others [10,14,16,2528].…”
Section: Methodsmentioning
confidence: 99%
“…An IQR increase in greenness was associated with 3.6 (95% CI: 1.2, 6.0) mmHg lower night time systolic blood pressure recorded with a blood pressure monitors among participants living in the same address their entire life in Belgium [15]. Among participants living at an address different from their birth address at the time of the measurement, only residential greenness exposure in early-life was associated with night systolic blood pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Mixed modeling was performed to investigate buccal telomere length in young adulthood and telomere tracking in association with covariates. To differentiate between early-life and adulthood exposure to traffic and greenness, we performed stratified analysis for twins who were living at the same address their whole life (non-movers, n = 62) and twins who were living at a different address than their birth address at the time of sample collection (movers, n = 122) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous evidence linked residential green spaces with cardiovascular health and cardiovascular risk factors. There is evidence that a high amount of green spaces is associated with a decrease in cardiovascular mortality [16], a lower hazard of CVD [17], a lower cardiovascular risk [18], and some cardiovascular risk factors, such as obesity [19] and high blood pressure [20]. However, there is no consistent pattern of associations with cardiovascular risk factors, especially in adults, as some studies found green spaces to be associated with a decrease in CVD risk factors while others found no associations [12,13].…”
Section: Introductionmentioning
confidence: 99%